2006
DOI: 10.1681/asn.2006050525
|View full text |Cite
|
Sign up to set email alerts
|

Connective Tissue Growth Factor Plays an Important Role in Advanced Glycation End Product–Induced Tubular Epithelial-to-Mesenchymal Transition

Abstract: Epithelial-to-mesenchymal transition (EMT) of tubular cells contributes to the renal accumulation of matrix protein that is associated with diabetic nephropathy. Both TGF-␤1 and advanced glycation end products (AGE) are able to induce EMT in cell culture. This study examined the role of the prosclerotic growth factor connective tissue growth factor (CTGF) as a downstream mediator of these processes. EMT was assessed by the expression of ␣-smooth muscle actin, vimentin, E-cadherin, and matrix proteins and the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
209
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(220 citation statements)
references
References 42 publications
7
209
0
4
Order By: Relevance
“…It is therefore possible that accumulated AGEs promote fibrosis in aged individuals and contribute to disease pathogenesis. Our study could explain why the fibrosis rate is higher in diabetes, for example, in the pathogenesis of diabetic nephropathy (Burns et al ., 2006). Furthermore, the similar effects of TGFβ1 and TGFβ2 on the AGE enhancement of EMT further suggests that basement membrane AGEs could play a role in TGFβ1‐mediated fibrosis, such as the cardiac and lung fibroses that occur in the diseases of these organs (Yuen et al ., 2010; Song et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore possible that accumulated AGEs promote fibrosis in aged individuals and contribute to disease pathogenesis. Our study could explain why the fibrosis rate is higher in diabetes, for example, in the pathogenesis of diabetic nephropathy (Burns et al ., 2006). Furthermore, the similar effects of TGFβ1 and TGFβ2 on the AGE enhancement of EMT further suggests that basement membrane AGEs could play a role in TGFβ1‐mediated fibrosis, such as the cardiac and lung fibroses that occur in the diseases of these organs (Yuen et al ., 2010; Song et al ., 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested a role for AGEs in EMT; kidney tubular epithelial cell EMT and fibrosis, which occur in diabetic nephropathy, are mediated through engagement of the receptor for AGEs (RAGE) with AGEs, followed by the synthesis of connective tissue growth factor and can be inhibited by AGE inhibitors (Oldfield et al ., 2001; Burns et al ., 2006; Sugimoto et al ., 2007). The AGE–RAGE interaction also enhances TGFβ1 expression and induces fibrosis of the peritoneal membrane (De Vriese et al ., 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Induction of TGF-b1 may convert tubular epithelial cells and fibroblasts into activated myofibroblasts, which may be responsible for increased deposition of interstitial matrix in response to TGF-b/Smad signaling. Furthermore, considerable evidence indicates that CTGF plays a pivotal role in TGF-b-dependent tubulointerstitial fibrosis (Gupta et al, 2000;Burns et al, 2006). CTGF mediates the up-regulation of collagen type I by TGF-b1 in mesangial cells and fibroblasts; however, it…”
Section: Discussionmentioning
confidence: 99%
“…The underlying pathology of EMT has since been observed in renal biopsies from diseased kidney where the proportion of cells undergoing transition correlated to both the level of serum creatinine and the degree of interstitial fibrosis [88]. Evidence for EMT in vivo has since been described in various forms of of CKD, including diabetic nephropathy [89] [90]. In diabetes, glomerular fibrosis is observed in the progression from incipient to overt nephropathy [6].…”
Section: Tgf-β1 Emt and Fibrosis In Diabetic Nephropathymentioning
confidence: 99%